2011
DOI: 10.1631/jzus.b1000402
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral hemilaminectomy for patients with intradural extramedullary tumors

Abstract: Abstract:A modified hemilaminectomy was introduced in an attempt to explore the operative techniques and the values of the limited approach to spinal cord tumors. Forty-five consecutive patients with intradural extramedullary lesions, who underwent modified hemilaminectomy, were studied retrospectively. The intraspinal tumors were removed via the limited bone window with a 3.3-cm mean length (range: 2.0-6.5 cm) and a 1.2-cm mean width (range: 0.6-1.5 cm), in which the inner parts of the medial and lateral lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 27 publications
5
26
1
1
Order By: Relevance
“…For these reasons, some authors have recently favored hemilaminectomy for resection of intraspinal lesions. 3,5,55,61,72 According to our review, the mean duration of preoperative symptoms was 29 months, substantially shorter than the 57-month average reported previously. 73 Furthermore, we found a statistically significant correlation between shorter duration of presurgical symptoms (≤ 3 months) and favorable clinical outcome.…”
contrasting
confidence: 61%
“…For these reasons, some authors have recently favored hemilaminectomy for resection of intraspinal lesions. 3,5,55,61,72 According to our review, the mean duration of preoperative symptoms was 29 months, substantially shorter than the 57-month average reported previously. 73 Furthermore, we found a statistically significant correlation between shorter duration of presurgical symptoms (≤ 3 months) and favorable clinical outcome.…”
contrasting
confidence: 61%
“…Sun et al . describe a potential use for UHIL in all lateral intradural lesions regardless of how ventral or lateral they sit; our dataset, although small, supports their proposal.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, many studies have demonstrated a strong association between standard laminectomy and post‐operative complications; namely, spinal deformity and damage to dissected structures during the approach. This relationship is particularly strong in pediatric subjects. In this clinical article, we present the operative techniques for UHIL and an evaluation of the effectiveness of this approach through analysis of a consecutive case series.…”
Section: Introductionmentioning
confidence: 99%
“…Hemilaminectomy+microscopic excision is advantageous in the removal of cervical schwannoma. However, the hemilaminectomy approach provides a relatively narrow view of the spinal intracanalar regions [18]; so, large intradural extramedullary schwannomas that require resection are difficult to manage by hemilaminectomy+microscopic excision.…”
Section: Discussionmentioning
confidence: 99%